Effect of Ralgro on the performance of cull beef cows - Corah, L.R.; Brazle, F.; Dawes, J.D. (Kansas State University. Agricultural Experiment Station, 2011)
We assigned 110 cull beef cows of mixed breeding to a control group and a group implanted with 36 mg Ralgro. Ralgro implants improved gains 12.8 lbs (11.2%) over a 59-day grazing period.
Keywords: Beef; Performance; Cull beef cows